Microwave-Assisted, Ionic Liquid-Catalyzed Synthesis of 1,2-Disubstituted Benzimidazoles under Solvent-Free Conditions - Duc, Dau; Giang, Le Duc (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 3, 2023)
An efficient method for the synthesis of 1,2-disubstituted benzimidazoles has been developed from 1,2‐diaminobenzenes and aldehydes using 1-butyl-3-methylimidazolium ([Bmim]BF 4 ) as a catalyst under solvent-free conditions. Various products were obtained in good to excellent yields under microwave irradiation. The synthesis features some advantages such as short reaction time, environmentally benign conditions, simple work-up procedure, and high efficiency.